Tribology in Manufacturing Technology - Davim, J. Paulo (Materials Forming, Machining and Tribology,, 2013)
The present book aims to provide research advances on tribology in manufacturing technology for modern industry. This book can be used as a research book for final undergraduate engineering course (for example, mechanical, manufacturing, materials, etc) or as a subject on manufacturing at the postgraduate level. Also, this book can serve as a useful reference for academics, manufacturing and tribology researchers, mechanical, mechanical, manufacturing and materials engineers, professionals in related industries with manufacturing and tribology.